Optimized D-α-tocopherol polyethylene glycol succinate/phospholipid self-assembled mixed micelles: A promising lipid-based nanoplatform for augmenting the antifungal activity of fluconazole - Badr-Eldin Shaimaa M.; Aldawsari Hibah M.; Fahmy Usama A.; Ahmed Osama A. A.; Alhakamy Nabil A.; Elfaky Mahmoud A.; Sirwi Alaa; Hawsawi Salman A.; Alzahrani Ali H.; Yaseen Abdulrahman Y.; Qassim Mohannad; Kotta Sabna (Acta Pharmaceutica)
Fluconazole (FLZ) is the most widely used antifungal agent for treating cutaneous candidiasis. Although oral FLZ has been proved to be effective, the incidence of side effects necessitates the development of an effective formulation that could surpass the pitfalls associated with systemic availability. Accordingly, this research aimed at developing a self-assembled mixed micelles topical delivery system to enhance the topical delivery of the drug. Self-assembled mixed micelles were developed using D-α-tocopheryl polyethylene glycol 1000 succinate and phospholipids and optimized using Box-Behnken design. The optimized formulation with minimized size was then tested in vivo for the antifungal activity against C. albicans in immunocompromised mice. Treatment with the optimized formulation led to decreased peripheral erythema as well as lesions due to fungal infection in comparison to raw FLZ loaded gel. Therefore, the developed formulation was found to be a promising vehicle for the treatment of cutaneous candidiasis.